The Augustinian Legacy of the Procreative Marriage: Contemporary Implications and Alternatives - Richie, Cristina (Feminist theology, 2014)
Augustine’s legacy, particularly his view of marriage as being primarily procreative and the sin of mutually desired non-procreative sex, has had a lasting impact on sexual theology and ethics in the Catholic Church. Yet indulging in the Augustinian legacy without reflection and regarding children as the end goal of marriage has led to the unchallenged assumption that children are needed in every marriage. I will examine the problematic concept of matrimony as a necessary producer of children through a variety of ethical lenses – the environmental, the feminist, and the bioethical – and provide an alternative to the procreative norm of sexual expression. By focusing on the unitive aspect of marital love instead of the procreative, partners are liberated to realize their union as fully mature, regardless of biological generation thus addressing ethical concerns and providing a theological alternative to the procreative marriage.